ANALISIS PENGARUH PROGRAM BANK SAMPAH TERHADAP PENDAPATAN NASABAH BANK SAMPAH DI KOTA DENPASAR - Prayati, Ni Made Via; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 6, Juni 2018 (pp. 1112-1351), 2018)
Increasing the number of residents, resulting in the city of Denpasar is not spared from the problem of increasing waste every day. Waste bank is one solution to reduce the existing garbage problem, because the garbage bank is an environment-based waste management that is done by recycling the waste into goods that have economic value. This study was conducted using primary data. The sample in this research is the society that become the customer in the garbage bank program located in every District in Denpasar City as much as 98 respondents with proportional stratified random sampling method. Data collection was done by interview, questionnaire and observation. Data analysis technique used is multiple linear regression analysis. Based on the results of analysis shows that simultaneously customer participation, waste saving and sales results have a significant effect on the income of customers of waste banks, while partially customer participation does not significantly influence and waste saving, sales results significantly influence the income of customers of garbage bank in Denpasar.   Keywords : Bank waste program, income